(untitled) - Bauman, Robert W. (San Francisco, 2004)
Microbiology by Robert Bauman features an unparalleled, visually stunning art program that works with the text to engage as it teaches. Filled with interesting vignettes, coverage of hot topics, and cutting-edge research, Bauman's text brings the wonders of microbiology alive while providing a solid, comprehensive introduction to the field. A complete introduction to all general microbiology topics. For college instructors, students, people in the nursing/allied health field, or anyone interested in microbiology.
Keywords: Microbiology